Impact of Take‐Back Regulation on the Remanufacturing Industry - Esenduran, Gökçe; Kemahlıoğlu‐Ziya, Eda; Swaminathan, Jayashankar M. (Production and Operations Management, 2017)
As waste from used electronic products grows steadily, manufacturers face take‐back regulations mandating its collection and proper treatment through recycling, or remanufacturing. Environmentalists greet such regulation with enthusiasm, but its effect on remanufacturing activity and industry competition remains unclear. We research these questions, using a stylized model with an original equipment manufacturer (OEM) facing competition from an independent remanufacturer (IR). We examine the effects of regulation on three key factors: remanufacturing levels, consumer surplus, and the OEM profit. First, we find that total OEM remanufacturing actually may decrease under high collection and/or reuse targets, meaning more stringent targets do not imply more remanufacturing. Consumer surplus and the OEM profit, meanwhile, may increase when OEM‐IR competition exists in a regulated market. Finally, through a numerical study, we investigate how total welfare changes in the collection target, what happens when the cost of collection is not linear, and what happens when IR products are valued differently by consumers.